The Function of Inversion - Birner, Betty J. (The Discourse Function of Inversion in English, 1996)
In this chapter, I present a unified account of the discourse function of inversion, based on my study of 1778 naturally-occurring tokens. After a review of the theoretical background from which the current approach derives, I argue that inversion serves an information-packaging function (Chafe 1976), linking relatively unfamiliar information to the prior context via the clause-initial placement of information which is relatively familiar (typically evoked or inferrable) in the current discourse. Drawing on work by Prince (1992), who distinguishes between the (assumed) familiarity of an element to the hearer and the familiarity of the element within the discourse, I show that it is discourse-familiarity that is relevant for inversion. I then use this result to argue for the status of inferrable information as discourse-old. The chapter concludes with a discussion of the implications of this study for current pragmatic theory.